Patient Safety and Health Workforce Training: Identifying Curriculum Gaps and Development Needs - Fatima Shumayleh; Rafique Othman; Shaukat Waseem (Inovasi Analisis Data, 2024)
Objective: This study aims to explore the association of healthcare workforce training with patient safety in public and private hospitals of Pakistan. In particular, it needs to determine any gap in curricula and the necessary development in training programs that could enhance patient safety practices.Methods: Survey conducted on 500 healthcare professionals working in Pakistan tested PATH through Structural Equation Modeling (SEM) analyzing six variables likely to impact patient safety outcomes.Findings: The findings indicate that training quality, worker preparedness, and organizational support measure as strong predictors of improved patient safety outcomes. In addition, workforce readiness was a complete mediator between other independent variables and patient safety enhancements. Two issues identified as keys to more effective patient safety practices were both curriculum gaps between patient safety knowledge and training standardization.Novelty: The research illuminates the areas of curriculum deficits in the healthcare workforce training systems across Pakistan that limit the extent to which patients are safe. For example, this research emphasises the importance of workforce readiness to addressing these gaps and ultimately achieving better safety outcomes. Finally, the application of SEM to assess complex relationships between variables represents another methodological contribution of this study.Research Implications: These findings suggest that there is a need in Pakistan for quality improvement of curricula, standardization of training programs, and better work readiness among new graduates of healthcare training programs. Closing these curriculum gaps with deliberate intention will pave the way for creating a culture of safety within healthcare organizations and ultimately to better patient care outcomes